Изменения некоторых показателей крови у карпов и сазанно-карповых гибридов при заражении гвоздичниковыми - Кулаковская, О.П.; Свирепо, Б.Г. (Вестник зоологии, 1967)
The cestoid worms Caryophyllaeus fimbrieeps and Khawia sinensis at the beginning of the vegetative period cause the decrease of blood serum total protein of young carp and sazan-carp hybrids. At the end of the vegetative period on Kh. sinensis invasion the decrease of the hemoglobin content is observed in carp and hybrids of the second generation. Besides, during this period in all fishes the increase of T-globulin content takes place, apparently, owing to cestode effect on a fish organism.